Total Physical Response (TPR) as an Intervention Strategy for Improving Arabic Vocabulary Retention Among Indonesian Students - Marsekal Rahman Hakiem; Muhammad Haris Luthfi (PPPBA, 2025)
This study investigates the effectiveness of Total Physical Response (TPR) as an intervention strategy for improving Arabic vocabulary retention among Indonesian-speaking students. Employing a quantitative quasi-experimental design, 157 seventh-grade students at an Islamic junior secondary school in Indonesia were assessed through pre-test and post-test measures using paired samples t-test analysis. Vocabulary knowledge was evaluated across four dimensions: pronunciation accuracy, listening comprehension, contextual knowledge application, and semantic interrelatedness. The 10 target vocabulary items encompassed action verbs, body parts, and concrete nouns suited to kinesthetic pedagogical application. The results demonstrated statistically significant improvement from pre-test to post-test (t = 4.62, df = 156, p less than .001), with students achieving an average vocabulary gain of 8.78 points, corresponding to an 18.04 percent improvement. Approximately 61 percent of participants demonstrated improved post-test performance. This research addresses a notable research gap, as bibliometric analysis of 43 international journal articles from Scopus revealed no existing empirical studies examining the relationship between TPR methodology and Arabic language learning specifically for Indonesian speakers. The findings support TPR as an effective pedagogical approach for enhancing foreign language vocabulary retention through physical engagement and embodied learning mechanisms. These results have significant implications for language educators seeking evidence-based interventions to improve vocabulary acquisition outcomes in multilingual educational contexts and suggest the need for systematic integration of kinesthetic-based instruction within Arabic language curricula.